Experiences of childhood emotional maltreatment and emotional intelligence in young women - Suslow, Thomas; Kersting, Anette; Hoepfel, Dennis (Frontiers in Psychiatry, 2025)
BackgroundResearch on the long-term consequences of childhood maltreatment underscores its contribution to impairments in cognitive-affective functions. According to trait models, emotional intelligence is subdivided into experiential abilities (emotion perception and thought facilitation through emotion) and strategic abilities (understanding and managing emotion). In the present study, we examined the relationship of emotional and other forms of childhood maltreatment with overall trait emotional intelligence and its specific facets in women with adverse childhood experiences.Materials and MethodsOur sample consisted of ninety-seven young women with experiences of childhood maltreatment as assessed with the Childhood Trauma Questionnaire (CTQ). Trait emotional intelligence was measured using the Self-Rated Emotional Intelligence Scale (SREIS). Participants’ verbal intelligence, cognitive flexibility, trait anxiety, and depressive symptoms were also assessed.ResultsEmotional neglect was negatively correlated with the SREIS subscale Understanding emotions. Regression analysis indicated that emotional neglect was a significant predictor of understanding emotion independent of women’s verbal intelligence, cognitive flexibility, trait anxiety, and depressive symptoms. Neither emotional abuse nor other CTQ subscales showed correlations with any of the SREIS scores.DiscussionExperiences of emotional neglect during childhood but not of other types of maltreatment seem to go along with a decreased ability to understand and verbalize emotional states in adulthood. Thus, early emotional neglect could have an impact on strategic emotional abilities. Emotional neglect may have a greater effect on the development and expression of emotional intelligence than emotional abuse.